Testosterone and cortisol in 93 elite road cyclists during a 10-day stage race: relationship with final ranking - Simonetto, L.; Fiorella, P.; Impellizzeri, F. M.; Giorgi, A.; Bonifazi, M. (Sport Sciences for Health, 2016)
Cycling stage racing is a heavy and strenuous endurance event and it has been recognized that such exercise can affect the hormonal asset of hypothalamic-pituitary-adrenal (HPA) and hypothalamic-pituitary-testicular (HPT) axis. However, in cycling, literature on such changes is scarce and published data have been derived from small samples of athletes. The aims of study were to provide normative values for serum hormonal steroid values, changes in serum hormonal steroids and assess any relationships between a riders` performance and their hormonal profile before and after the stage race. Male elite professional cyclists (n = 93) competing in the 2010 GiroBio 10-day stage race participated in this study. Blood chemistry measurements included cortisol (C), testosterone (T), free testosterone (fT) and sex hormone binding globulin (SHBG). Data are expressed as mean ± SD. Serum concentration of C and fT were lower at the end of GiroBio [C (nmol L-1): 559.34 ± 95.71 vs 469.59 ± 51.12; fT (pmol ml-1): 63.91 ± 27.85 vs 37.51 ± 17.86]. These serum hormonal (mean values ± 2SD) values may be near the physiological ceiling for elite cyclists. There was inverse correlation among average final speed and pre-competition serum concentration of T (r = -0.265, p = 0.01); average final speed was negatively correlated with riders body mass pre and post the 10-day stage event. In conclusion, pre-GiroBio serum C levels could be a useful benchmark to preserve riders` health and, moreover, our data confirm that the strenuous effort sustained by riders during a stage race induces appreciable changes in the hormonal profile. In addition, our data suggest that lower levels of T could represent favourable prerequisite to cope better in a cycling stage race.